Synthesis of Lead Oxide Using the Oxidizing Agent (NH4)2S2O8 with Variaous Amounts of NaOH for Decolorization of Remazol Black B Solution - Meiske Erdinarini Anggita; Abdul Haris; Didik Setiyo Widodo (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
In this study, the lead oxide has been successfully synthesized using oxidizing agents (NH4)2S2O8 and applied to decolorize the Remazole Black B (RBB) solution. Lead oxide was synthesized by the batch method through the mechanism of reduction-oxidation and characterized using SEM-EDX and XRD. Decolorizing RBB solution was performed using a modified Fenton method. This study aims to determine the optimum performance of RBB decolorization from lead oxide. The results showed that the crystal formed contains Pb and O. Pb oxide obtained was α-PBO2 with the orthorhombic crystal system. Based on characterization, the lead oxide obtained has a surface morphology of coral flowers-like. Synthesis utilizing equilibrium composition (1:2) and a drying temperature of 100°C yielded Pb oxide, which has a better potential as a modifier in RBB decolorization with a decolorization percentage of 80.07%. The process was then carried out for advanced synthesis less and excess of molar variations. The ratio of lead oxide: NaOH (1:4) showed optimum performance in decolorizing RBB with a decolorization percentage of 80.07 %.